Height Growth of Korean Pine Seedlings Planted under Strip-Cut Larch Plantations in Northeast China - Toshiaki Owari; Shinichi Tatsumi; Liangzhi Ning; Mingfang Yin (International Journal of Forestry Research)
To develop two-storied forest management of larch plantations in Northeast China, this study examined the height growth of Korean pine (Pinus koraiensis Sieb. et Zucc.) seedlings planted under strip-cut larch canopies. We measured the height growth of the underplanted seedlings 4 years after planting. The larch canopies were of varying stand age (12, 17, and 37 years) and strip-cut width (4.5, 6.0, and 7.5 m). We measured the seedling height growth in an open site (i.e., a site with no canopy). Underplanted seedlings had a smaller height growth (12.1–20.1 cm year−1) than the seedlings planted in the open site (23.7 cm year−1). The seedlings underplanted in the wider strip-cuts tended to have greater height growth than the seedlings underplanted in the narrowest strip-cuts. A generalized linear mixed model analysis predicted the greatest seedling height growth in the open site. A 36–47% reduction in annual height growth was predicted for the narrowest strip-cuts (4.5 m) versus the open site, while a 13–36% reduction in annual height growth was predicted for the wider strip-cuts (6.0–7.5 m) versus the open site. To maintain adequate height growth, forest managers are recommended to create wider strip-cuts (i.e., ≥6.0 m) for the purpose of underplanting Korean pine seedlings in larch plantations.